The scrapbook media quality and effectiveness: Motivation of biology students senior high school - Yusnaeni Yusnaeni; Felanda Ratu; Mbing Maria Imaculata; Sudirman Sudirman (JPBIO (Jurnal Pendidikan Biologi), 2020)
Motivation has an important role in improving learning quality. Scrapbook media can be an alternative learning media because it can be equipped with stimulus images that can attract interest and stimulate learning motivation. This research was a research development by adapting the ADDIE model. Scrapbook validity is measured from the results of expert and empirical validation. Expert validation includes media experts and material experts, while empirical validation by teacher and student. Product quality is the result of the implementation and the responses by students and teachers. Scrapbook effectiveness is seen from the increase in students' learning motivation when learning to use scrapbook. The instruments used were: teacher and student interview guidelines, material and media expert validation, field validation for teachers and students, and student motivation. Data were analyzed descriptively. The results showed that the quality of the scrapbook media was stated to be very valid with an average rating was 3.725 expert validators and the empirical validator was 3.45 with a valid category. The results of the implementation of the scrapbook media on total student learning motivation also increased by 24.80%, and the highest increase was in the aspect of initiative in learning which amounted to 33.40%.Keywords: Learning motivation, learning media, scrapbook